Frequency of Diabetes Mellitus in Females with Breast Cancer - Imran, Ragda; Ali, Haider; Arslan , Muhammad (Indus Journal of Bioscience Research, 2025)
Objective: “To determine the frequency of diabetes in patients with breast cancer. Study Design: Cross sectional study. Place of study and duration: Department of Medicine, Shaukat Khanum Memorial Cancer Hospital & Research Center Lahore for 6 months from 1st July 2024 to 31st December 2024. Patients & Methodology: One hundred and forty patients with breast cancer were enrolled through non-probability consecutive sampling technique. About 3ml blood sample was taken for assessment of HbA1c. Reports were assessed and if HBA1c>6.5%, then diabetes was labeled. Results: In this study the mean age of the participants was 50.84 ± 8.61 years, with a mean BMI of 24.48 ± 3.94 kg/m² and 42 (30%) had hypertension. A family history of breast cancer was reported in 25 (17.9%) participants. among 140 breasts cancer females 27 (19.29%) were diabetics. Diabetes was present in 4 (5.9%) patients aged ≤50 years, while in 23 (31.9%) older than 50 years (p-value